Applications of Operation research in the Field of IOT (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
These days Internet of Things (IoT) increased an extraordinary consideration structure specialist, since it turns into a significant innovation that guarantees a shrewd individual life, by permitting an interchanges between objects, machines and each thing together with people groups. IoT speaks to a framework which comprises a things in reality, and sensors joined to or consolidated to thesethings, associated with the Internet through wired and remote system structure.In this paper I have represented the various application of the operation research in the field of IoT.